1997
DOI: 10.1007/bf03164764
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of99mTc-Technegas SPECT with133Xe dynamic SPECT in pulmonary emphysema

Abstract: This study was undertaken to compare axial images of 99mTc-Technegas SPECT (Technegas) with those of 133Xe gas dynamic SPECT in patients with pulmonary emphysema. There were 20 patients, 19 males and 1 female. All patients except one ex-smoker were heavy smokers with a mean age of 68.1 years. For Technegas scintigraphy, the patients inhaled 505 MBq 99mTc-Technegas in several tidal volume breaths in the supine position without breath holding. For 133Xe gas scintigraphy, the patients inhaled 370 MBq 133Xe gas. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…pulmonary emphysemaâ€"evenmild abnor malitiesâ€"than does CT and reveal ventila tion impairment more easily than does xenon-133 dynamic SPECT [13,15]. On the other hand, pathologic changessuch as emphysemaand bulla formation result mainly in obstructive pulmonary impairment.…”
mentioning
confidence: 99%
“…pulmonary emphysemaâ€"evenmild abnor malitiesâ€"than does CT and reveal ventila tion impairment more easily than does xenon-133 dynamic SPECT [13,15]. On the other hand, pathologic changessuch as emphysemaand bulla formation result mainly in obstructive pulmonary impairment.…”
mentioning
confidence: 99%
“…2-15 Satoh et al reported the usefulness of Technegas SPECT to diagnose pulmonary emphysema. [12][13][14] In addition, Zhang et al reported that an index expressing the subliminal heterogeneous distribution by Technegas SPECT correlates well with the severity of silicosis. 15 There are however, no reports which evaluate the usefulness of Technegas to diagnose bronchial asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Technegas [12][13][14] Technegas was generated in a proprietary generator (Technegas Generator, Tetley Manufacturing Ltd., Sydney, Australia) by the resistive heating of a graphite crucible up to 2,500°C in which a saline solution of 505 MBq of Tc-99m pertechnetate was added and then the mixture was dried. After Technegas was generated in an atmosphere of 100% argon, it was dispersed in a leadlined chamber.…”
Section: Bronchofiberscopy and Bronchial Biopsymentioning
confidence: 99%
“…On the other hand, as functional imaging, recently ultrafine 99m Tc-labelled carbon particles are being used for ventilation scintigraphy including single photon emission computed tomography (SPECT) [2][3][4][5][6][7][8][9][10][11][12]. Burch et al [2] reported that 99m Tc-Technegas (Technegas) has a considerably small particle size and can reach the peripheral parts of the lung.…”
Section: Introductionmentioning
confidence: 99%